EFEK MEDIASI STRUKTUR MODAL TERHADAP KINERJA KEUANGAN BERLANDAS UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN - Eka Kurnia Patmasari; Kesi Widjajanti; Ardiani Ika Sulistyawati (JURNAL STIE SEMARANG, 2022)
This study was conducted to examine the effect of company size and sales growth on the company's financial performance through capital structure as an intervening variable. The purpose of this study is to measure and analyze the effect of company size and sales growth on the company's financial performance through capital structure as an intervening variable in various industrial sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The population in this study were 174 companies listed on the Indonesia Stock Exchange for the period 2017 – 2019. Then, 27 companies were taken according to the criteria so that a total of 81 samples were taken. The analysis technique uses Structural Equation Modeling (SEM) with Partial Least Square (PLS). The results showed that the relationship between company size and sales growth had no effect on the company's financial performance, but the capital structure had a positive and significant effect on the company's financial performance. This study also shows that company size and sales growth have no effect on capital structure.